Antiglucocorticoid therapy for older adults with anxiety and co-occurring cognitive dysfunction: results from a pilot study with mifepristone - Lenze, Eric J. (2014)
OBJECTIVES: In older adults with anxiety disorders, chronically elevated cortisol may contribute to cognitive impairment and elevated anxiety. We conducted a pilot study with mifepristone, a glucocorticoid receptor antagonist, as a potential treatment for late-life anxiety disorders and co-occurring cognitive dysfunction. METHODS: 15 individuals aged 60+ with an anxiety disorder plus cognitive dysfunction participated in the 12 week study. In the first week, participants were randomly assigned to mifepristone 300mg daily or placebo. In the subsequent 3 weeks, all participants received mifepristone 300mg. Mifepristone was then discontinued, and the participants were reassessed 8 weeks later. We examined (1) cognitive changes; (2) worry symptom severity; (3) safety and tolerability; and (4) salivary cortisol before, during, and after mifepristone exposure. RESULTS: Overall safety, tolerability, and high retention supported the feasibility of this research. Participants with higher baseline cortisol levels (peak cortisol >6.0ng/ml, n=5) showed improvements in memory, executive function, and worry severity after 3–4 weeks of mifepristone with persistent memory and worry improvements 8 weeks after mifepristone discontinuation. Individuals with low to normal baseline cortisol (n=8) showed little to no improvement. As expected, cortisol levels rose during mifepristone exposure and returned to pre-treatment levels 8 weeks after mifepristone discontinuation. In the first week of treatment, there were no differences between placebo-treated and mifepristone-treated participants. CONCLUSION: The results of this pilot study warrant further testing of antiglucocorticoid agents in late-life anxiety disorders with co-occurring cognitive dysfunction. Mifepristone is hypothesized to have benefits in patients with evidence of glucocorticoid excess. Directions for further study are discussed.